An open source QGIS-based workflow for model application and experimentation with aquatic ecosystems. (September 2017) - Nielsen, Anders; Bolding, Karsten; Hu, Fenjuan; Trolle, Dennis
Abstract: We present the new Water Ecosystems Tool (WET), a workflow implemented (as a plugin) in QGIS, for application and evaluation of aquatic ecosystem models. WET provides a Graphical User Interface (GUI) for the coupled one-dimensional hydrodynamic-ecosystem model GOTM-FABM-PCLake. WET is unique as it enables a standardized and easy-to-use workflow for an otherwise complex model application and is readily applicable to any individual lake and reservoir in the world. WET integrates a platform for model experimentation through scenario simulations – currently encompassing changes in climate and nutrient loads. WET also includes a link to the SWAT (Soil & Water Assessment Tool) watershed model, which can be used to simulate how land use changes affect aquatic ecosystems. The tool is open source and may therefore be readily expanded and adapted for additional model experimentations.